Islamic Spirituality Movement and Its Implications on Social and Political Ethics in Indonesia - DALMERI; RATONO (International Journal of Islamic Thought, 2016)
In the nineteenth century, Islamic religious movements fell into three groups: First, those advocating salvation through revivalism as exemplified by Wahhabism; Second, salvation through the prophecy of divinely-sent leader (or guide) as seen in the case of Mahdism; and third, salvation through ecstasy and loss of self-volition, such as in the Sufi Shaykh (charismatic leader), characteristic of the tariqa revival. This article explains about the attitudes of reformers towards Sufism varied from the hostility of Muhammad ibn ‘Abd al-Wahhab who was against bid‘a; the ‘Salafi’ movement, i.e Muhammad ‘Abduh and Rashid Rida, who were against Sufism but tolerated the ethical teachings of al-Ghazali; and Mustafa Kemal in Turkey who banned Sufi orders outright in 1925. In recent Indonesia milieu, some prominent figures have shown their interest in Sufism, but certain Muslim organizations or institutions to some extent are against it such as Hizbut Tahrir Indonesia, Sabili Magazine, Salafy Journal, Muhammadiyyah, and Persatuan Islam.